Best Approximation In Linear K-Normed Spaces - et. al., Alaa Adnan Auad, (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2021)
The article describes a new idea and established the concept the existence and uniqueness for best approximation in linear k-normed spaces, proved the mapping form k-normed space into finite dimensional subspace of k-normed space is continuous , bounded compact subset of linear k-normed is proximal and characterization of best uniform approximation in same space.